Analysis of the waiver of bidding based on value in the Alagoas Military Police: Solutions to avoid illegal splitting of expenses (Research, Society and Development, 2025)
The Brazilian legal system establishes the obligation to bid for public administration to acquire goods and contract services. In contrast, laws 8,666 of July 21, 1993 and 14,133 of April 1, 2021, both legal provisions currently in force in Brazil, establish some conditions under which this obligation is mitigated. Among these possibilities is the waiver of bidding due to low value. It is common practice among public procurement sectors to use this resource as a way of reducing bureaucracy; however, the operator must have legal knowledge so that he or she does not incur the infamous illegal splitting of expenses and, consequently, a crime provided for in the bidding law. This reality was studied within the scope of the Military Police of Alagoas (PMAL), using field research, carried out quantitatively on the report of the activities carried out by the Logistics Support Directorate during the year 2021 and qualitatively through an interview with the Chief Officer of the Corporation's purchasing sector. Documentary research was also carried out in national legislation and specialized literature. Our objective was to analyze the bidding process when it is waived in the PMAL, due to the value of the good or service to be acquired, and to present solutions to avoid the illegal splitting of expenses. It was found that, in fact, this is the main form of contracting at Briosa. Alternatives to this practice were presented, among which, mainly, the use of the Price Registration System.